Aktualisasi Hadis al-Hawari dalam Supervisi Akademik Berbasis Digital di MIS Bahrul Ulum 2 Bojonegoro - Rahmawati, Nova Fadliana; Farih Annisa Putri, Farih Annisa; Sahudi, Sahudi (Program Studi Manajemen Pendidikan Islam, 2023)
Contemporary madrasah leadership demands a transition toward competency based delegation, collaborative supervision, and digital accountability. This qualitative case study at MIS Bahrul Ulum 2 Bulu Bojonegoro analyzes the implementation of task allocation and academic supervision interpreted through the ethical lens of the al-hawari prophetic tradition. Data collected via interviews, observations, and documentation were analyzed interactively. The findings indicate that task assignment is structured through integrative planning and digital instruments, while academic supervision operates cyclically from planning to teacher rotation. However, efficiency is constrained by time limits, external commitments, and workload imbalances. Theoretically, the al-hawari tradition serves as an ethical framework for selecting trusted personnel, defining responsibilities, and recognizing performance rather than personal loyalty. This study conceptualizes the 5A Prophetic Delegation Model, Amanah, Ahli, Adil, Akuntabel, and Apresiatif, as a strategic framework to enhance madrasah academic supervision.